(3GdGNJjGQGJs - (3Ydj Hf CMeO Hf eMeO GdLeGdj GdHcQj , YdGA GdOjf,J (B932 (3g` s ((3GdbOS GdTQja s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYde YdekG dgOGjI GdYGdejf Hefg GdhGai hTQM Hg UOhQ GdYGdejf Ydi ebJVi Ydeg GdeMjW s
(3BNQgG (B:s
(3agh HWQjb GdeLGR ddehGabI hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH Je GdcJGH HYhf Gddg hMSf Jhajbg s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B25 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B742s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3Gdabg GdMfajs